Creating Safety in Primary Care Practice with Electronic Medical Records Requires the Consideration of System Dynamics. Issue 1 (12th April 2011) - McEwen, Timothy R.; Elder, Nancy C.; Flach, John M.
Abstract : Improvement in quality and safety in health care often depends on eliminating errors. Using examples from our research on the medical testing processes in primary care medical practices, we argue that designing safer systems requires moving beyond frameworks that focus exclusively on error elimination to consider the broader system dynamics including information loops that can be critical to the overall stability of the system. We focus on describing the nature of information coupling in relation to the constructs of essential friction, autonomation, and ecological interface design and how these can lead to more resilient systems. With the recent push in the United States to move towards electronic medical records (EMR), we conclude with suggestions for improving EMR systems based on these concepts.